The northern renaissance 1400-1550 (Northbrook, Ill. Roland Collection, 1986)
Features works of Jan Van Eyck, Robert Campin, Dirk Bouts, Gerard David, Jan Provoost, Geertgen, Hans Memlinc, Van der Weyden, Hieronymous Bosch, Peter Bruegel, Marinus, Lucas Cranach, Jan Gossaert, Albrecht Durer, Hans Holbein.
VHS format.
Director, Henry Lewes ; writer/narrator, Edwin Mullins.
Keywords: Painting, Renaissance -- Flanders; Painting -- History -- Netherlands; Art, Flemish; Art, Dutch